2013
DOI: 10.1002/oa.2313
|View full text |Cite
|
Sign up to set email alerts
|

The Movement and Exchange of Dogs in the Prehistoric Caribbean: An Isotopic Investigation

Abstract: This study explores the feasibility of using strontium isotope ( 87 Sr/ 86 Sr) analyses of enamel from domestic dogs (Canis familiaris) to investigate networks of exchange in the prehistoric Circum-Caribbean. Dog teeth were obtained from burial and domestic contexts from two prehistoric sites (Anse à la Gourde and Morel) on Grande-Terre, Guadeloupe (Lesser Antilles). Strontium isotope results were compared with local biosphere 87 Sr/ 86 Sr data at the scale of the site, island and archipelago. The isotope resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
2
27
0
2
Order By: Relevance
“…Previous research has revealed that a substantial proportion (>25%) of the human population at Anse à la Gourde are nonlocals (Booden et al 2008;Hoogland, Hofman, and Panhuysen 2010;, as well as one of the three dogs from this site and two out of seven dogs at Morel (Laffoon et al 2015 (Laffoon 2012;) based on measurements of archaeological rice rat enamel (n = 10), human bone (n = 8), and soil (n = 4) samples.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Previous research has revealed that a substantial proportion (>25%) of the human population at Anse à la Gourde are nonlocals (Booden et al 2008;Hoogland, Hofman, and Panhuysen 2010;, as well as one of the three dogs from this site and two out of seven dogs at Morel (Laffoon et al 2015 (Laffoon 2012;) based on measurements of archaeological rice rat enamel (n = 10), human bone (n = 8), and soil (n = 4) samples.…”
Section: Resultsmentioning
confidence: 83%
“…New multi-isotope evidence (both strontium and carbon) is presented from both the human and dog samples from El Cabo (humans n = 3; dogs n = 2) and El Flaco (humans n = 5; dogs n = 2), and from the human samples from Morel (n = 7), as well as the enamel carbon isotope results for the Morel (n = 3) and Anse à la Gourde (n = 3) dog samples. These data are compared to, and interpreted in conjunction with, previously published strontium isotope results from the human population at Anse à la Gourde (Booden et al 2008;Hoogland, Hofman, and Panhuysen 2010;) and the dog collections from both Anse à la Gourde and Morel (Laffoon et al 2015) and build upon a limited data set of enamel carbon isotopes from Anse à la Gourde (Laffoon, Valcárcel Rojas, and Hofman 2013) and the wider Caribbean (Table 1).…”
Section: Study Sites and Samplesmentioning
confidence: 98%
See 3 more Smart Citations